Prevalence and significance of fragmented QRS complex in lead V1 on the surface electrocardiogram of healthy athletes. Issue 4 (25th February 2020) - Ollitrault, Pierre; Pellissier, Arnaud; Champ-Rigot, Laure; Junqua, Nicolas; Chequel, Mathieu; Reboursiere, Emmanuel; Saloux, Éric; Milliez, Paul; Hodzic, Amir
Abstract: Aims: Limited data exist concerning fragmented QRS complexes (fQRSs) on the surface electrocardiogram (ECG) of apparently healthy athletes. We aimed to study the prevalence and significance of fQRS in lead V1 (fQRSV1 ), representing right ventricular (RV) activation, regarding training-induced RV morphological remodelling. Methods and results: Between January 2017 and August 2019, 434 consecutive non-sedentary subjects underwent preparticipation cardiovascular screening, including a 12-lead ECG. Three hundred and ninety-three apparently healthy subjects were included, 119 of them were athletes (defined as performing ≥8 h/week for the last 6 months) and 274 were non-athletes. All athletes underwent two-dimensional transthoracic echocardiography. Fragmented QRS complex in lead V1 pattern was defined as a narrow (<120 ms) and quadriphasic QRS complex in lead V1 . Fragmented QRS complex in lead V1 was more frequent in athletes compared with non-athletes (22% vs. 5.1%, P  < 0.001) and was independently associated with the athlete status [adjusted odds ratio (aOR) = 4.693, 95% confidence interval (95% CI) 2.299—9.583; P  < 0.001], the endurance category (aOR = 2.522, 95% CI 1.176—5.408; P  = 0.017), and age (aOR = 0.962, 95% CI 0.934–0.989; P  = 0.007) in multivariate analysis. In the subgroup of athletes, fQRSV1 was independently associated with mean RV outflow tract diameter (aOR = 1.458, 95% CI 1.105–1.923; P  = 0.008) and age (aOR = 0.941, 95% CI 0.894–0.989; P  = 0.017) in multivariate analysis. Conclusion: Fragmented QRS complex in lead V1 is a newly described, frequent, ECG pattern in young and apparently healthy athletes and is associated with training-induced RV remodelling.